Performance Study of The Training The Trainers Programme - Mit, Edwin; Juan, Sarah Samson; Suriati Khartini, Jali; Lee, Jun Choi (2010)
Performance measurement is a regular process involving the systematic collection, analysis and reporting of data that tracks resources used, work produced and whether specific outcomes were achieved. A particular reason for measuring training performance is that telecentre community needs a more competitive approach to sustain the training techniques used. In this paper, we are going to discuss on our training methodology that has been used in several telecentres (e.g., e-Lamai, Sarawak, and e-Buayan, Sabah), present the training metrics conducted at the telecentres, evaluate our training approaches based on training